Γ-Valerolactone from pyrolysis of calcium salts of levulinic-formic acid mixtures derived from cellulose. (January 2015) - Amarasekara, Ananda S.; Wiredu, Bernard; Edwards, Dre'Langala N.
Abstract: Hydrothermal degradation of cellulose (DP ∼ 450) in 0.02–0.20 mol dm −3 aq. hydrochloric acid at 160 °C, for 2–8 h and neutralization of the filtrate with calcium hydroxide can be used to prepare a mixture of carboxylic acid calcium salts. The mixture consists of calcium levulinate and calcium formate in approximately 1:0.65 mol ratio, together with CaCl2 . Pyrolysis of this crude mixture at 350 °C for 3.0 min produces pyrolyzate oil yield of 140–210 g kg −1 of dry salt mixture. The pyrolyzate was identified as ∼97% γ-valerolactone, with the minor products; levulinic acid, 3-methyl-2-cyclopentenone, and 2, 3-dimethyl-2-cyclopentenone by using a combination of GC–MS and NMR spectroscopy. Highlights: Degradation of cellulose and neutralization with Ca(OH)2 gives calcium salt mixture. Salt mixture consists of calcium levulinate: formate in ∼1:0.6 mol ratio. Pyrolysis of the salt mixture at 350 °C gives γ-valerolactone as the main product.